Case studies in abnormal psychology - Oltmanns, Thomas F.; Martin, Michele T.; Neale, John M.; Davison, Gerald C. (John Wiley & Sons, Inc., 2015)
"Case Studies in Abnormal Psychology, 10th Edition, takes mental disorders from the realm of theory into the complex reality of human lives. This casebook presents comprehensive coverage of 23 high interest cases that include topics such as eating disorders, gender identity disorder, borderline personality, and post traumatic stress disorder. Each study (1) provides detailed descriptions of a range of clinical problems, (2) illustrates some of the ways in which these problems can be viewed and treated, and (3) discusses some of the evidence that is available concerning the prevalence and causes of the disorders in question"-- Provided by publisher.